2021
DOI: 10.3389/fdmed.2021.763308
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Signaling in Periodontal Disease

Abstract: Periodontitis is a multifactorial and chronic condition associated with the formation of a dysbiotic biofilm, leading to a pro-inflammatory environment that can modulate cell signaling. The Wnt pathway plays fundamental roles during homeostasis and disease, and emerging evidence suggests its involvement in the maintenance of the periodontium and the development of periodontitis. Here, we summarize the role of the Wnt/β-catenin and non-canonical Wnt signaling pathways in periodontitis. The accumulated data sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 90 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…Initial comparisons between nociceptor-ablated and cre-control periapical lesion transcriptomes revealed that nociceptor-ablated females expressed a greater number of differentially expressed genes after 14 days of infection. Notably, nociceptors regulated the expression of key genes in Wnt signaling pathways, a mechanism known to be crucial in bone development and homeostasis (González-Quintanilla et al, 2021). After 14 days of infection, nociceptor-ablated females exhibited greater levels of Wnt7b and Wnt4, whereas cre-control females expressed more significant levels of Dkk1.…”
Section: )mentioning
confidence: 99%
“…Initial comparisons between nociceptor-ablated and cre-control periapical lesion transcriptomes revealed that nociceptor-ablated females expressed a greater number of differentially expressed genes after 14 days of infection. Notably, nociceptors regulated the expression of key genes in Wnt signaling pathways, a mechanism known to be crucial in bone development and homeostasis (González-Quintanilla et al, 2021). After 14 days of infection, nociceptor-ablated females exhibited greater levels of Wnt7b and Wnt4, whereas cre-control females expressed more significant levels of Dkk1.…”
Section: )mentioning
confidence: 99%